2020
DOI: 10.1007/s00038-020-01358-7
|View full text |Cite
|
Sign up to set email alerts
|

Does unwanted pregnancy lead to adverse health and healthcare utilization for mother and child? Evidence from low- and middle-income countries

Abstract: Objectives Unwanted pregnancy is an important public health concern in low-and middle-income countries (LMICs). Using a pooled dataset from 48 Demographic Health Surveys conducted in Africa, Asia, Latin America and Europe (n = 494,778), we examined the effect of unwanted pregnancy on maternal and child healthcare utilization and child health outcomes in LMICs. Methods We used logistic regression models to estimate the effect of unwanted pregnancy on antenatal care use, supervised delivery, childhood vaccinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 28 publications
2
20
2
Order By: Relevance
“…In this study, mothers with wanted type pregnancy were 75% less likely [AOR = 0.25, 95% CI: 0.14, 0.448] to became undernutritioned than those with unwanted pregnancy. This finding is similar to the evidence from low- and middle-income countries which indicated that unwanted pregnancy can affect maternal nutrition, health service, and child nutrition [ 23 , 24 ]. This is because mothers with wanted pregnancy type have planned programs on how to feed themselves and prepare to have diversified food types in their homes.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, mothers with wanted type pregnancy were 75% less likely [AOR = 0.25, 95% CI: 0.14, 0.448] to became undernutritioned than those with unwanted pregnancy. This finding is similar to the evidence from low- and middle-income countries which indicated that unwanted pregnancy can affect maternal nutrition, health service, and child nutrition [ 23 , 24 ]. This is because mothers with wanted pregnancy type have planned programs on how to feed themselves and prepare to have diversified food types in their homes.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is similar to evidence from low- and middle-income countries indicating that unwanted pregnancies can affect maternal nutrition, health service, and child nutrition. 22 , 33 This could be associated with women’s demand to invest in their pregnancy or spouse support as a result of their planned pregnancy. We were surprised that women who did not participate in Women’s Health Development Army meetings were more likely to be undernourished than their counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…A rise in contraceptive prevalence rate and the decline in unmet need for family planning significantly reduces maternal mortality and disability associated with complications of pregnancy and child birth [ 5 – 11 ]. Despite this fact, unacceptably millions of women suffer from unintended pregnancies (both mistimed and unwanted) and related consequences worldwide every year [ 9 – 12 ].…”
Section: Introductionmentioning
confidence: 99%